(untitled) (Palestine Technical College Journal for Research and Studies, 2019)
The study aimed to recognize the values of belonging and loyalty included in the Palestinian folk proverbs and their role in strengthening the relationship with Palestine. The study adopted the content analysis as a technique of the descriptive analytical method. The study sample consisted of 70 folk proverbs collected from the tongues of the elderly in Gaza Strip. The study found that there are many values of belonging and loyalty as sticking to the roots, sanctification of kinship, sacrifice, steadfastness, persistence, dignity, rejection of injustice and resistance to the usurper. The study also found that Islam orientated the folk proverbs by enhancing the noble values and directing of some values and expanding their concepts and there holistic circle and then refusing of the corrupted values. The Study recommended to give more concern about the folk proverbs and more concern about teaching and studying them.